P-229 Qelca© (quality end of life care for all): an innovation in end of life care education – delivered by the south london hospice education collaborative (slhec). Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Bryan, Liz; Berg, Jane; Reed, Liz; King, Helen; Vandeweghe, Maaike; Linehan, Gail; Menezes, Toni; Roots, Susan; Hackett, Jacquie; Moback, Berit
Abstract : Background: Eight hospices (adult and paediatric) are collaborating to plan, deliver and evaluate end of life care training. The benefits include: Pooling of resources, knowledge, capacity Improved sustainability Joint funding bids Robust evaluations. QELCA © Programme The aim: To empower participants to return to their working environment to lead change in practice, improving quality of care QELCA© is a multi-professional course consisting of five days of practical (participating and observing) and theoretical (listening, reflecting and debating) learning activities and six months action learning (AL) in the workplace. The aim of the AL is to support implementation of planned changes for self, team and organisation. It is delivered to small groups of learners from the same organisation/team. The programme is delivered by specialist clinicians who have attended a two day train the trainer course. With funding from Health Education South London (HESL) QELCA© has been adapted to enable clinicians from a range a care providers (acute, community, care homes, prison, psychiatry, paediatric, GPs) to attend. Evaluation: Using a mixed method of longitudinal approach all participants will be surveyed at baseline, six and 12 months asking about aims of undertaking QELCA© and the Self-efficacy in Palliative Care Scale (SEPC) (assessing efficacy in communication, patient management and multi-professional team working) (Mason, Ellershaw, 2004). A subsample of 20 participants will be interviewed at the same time points to explore their experience using a semi-structured approach. Findings will be reported in 2017.